Language Registers in Maritime Communication: A Study of Effective Messaging - Sunarlia Limbong; Novianty Palayukan; Ade Chandra; Frans Tandibura; Randy Ruslan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study identifies and analyzes the use of language registers in maritime communication on board ships. Employing a descriptive qualitative method, primary data were obtained through observation and interviews with the ship crew. Results indicate three commonly used language registers: formal (for daily interactions among crew to foster relaxed relationships), and technical (for operational and technical matters like engine maintenance and navigation). Appropriate use of these registers enhances effective messaging, improving ship safety and operational efficiency. This research contributes to developing more effective and safe maritime communication standards. Benefits include increased safety and efficiency, improved crew communication quality, and contributions to maritime standards.